Screw-Pine Biodiversity Conservation and Management in Sri Lanka - Miraaj, R.; Sujeethasai, K.; Vidhya, M.P. (University of Jaffna, 2026)
Plants of the Pandanus tectorius genus or screw-pines belong to the family Pandanaceae are found throughout Southeast Asia and Pacific islands. It has been observed in Sri Lanka's wild and coastal regions. The plant is also frequently planted as an ornamental in various places, particularly in Sri Lankan hotels and resorts. The animals and birds living along the coast find refuge in this pandanus environment. This versatile plant is used to make woven goods, medicine, staple foods, and building materials. Several aspects of this plant are beneficial to the local population. The objectives of this research are to protect biodiversity in its native environments, stop the degradation of coastal screw pine ecosystems, and strengthen the Sri Lankan economy by utilizing their products. This thorough analysis is based on online videos, webcasts, podcasts, and peer reviewed publications. There aren't any significant risks to the screw- pine ecology, and this species is common in Sri Lanka. Thus, the IUCN Red List of Threatened Species assigns the plant the classification of "Least Concern". Both aromatherapy and traditional medicine use the plant's oil to treat pain and nerve weakness. Over time, there has been a significant increase in the demand for screw pine. Due to their valuable essential oil, screw-pines have proven to be especially susceptible to exploitation. In certain places, these plants are also chopped down to construct resorts. These plants will be regarded as threatened species in the future as a result. Due to their greater ability to thrive in a variety of soil types and temperatures, it is necessary to urge the public to cultivate these plants both naturally and artificially. This study provides information on how to conserve pandanus plants in their natural environment, reduce the frequency of natural disasters that these wetlands plants help to prevent, cultivate a lot more
Keywords: Pandanus tectorius; Pandanaceae; Screw-pine; Biodiversity; Conservation